THE RELATIONSHIP OF KNOWLEDGE ABOUT THERAPEUTIC COMMUNICATION WITH THE APPLICATION OF THERAPEUTIC COMMUNICATION IN NURSE PROFESSION STUDENTS STIKES MEDISTRA INDONESIA IN 2022 - Putri, Intan; Indrawati, Lina; Baltasar S. S. Dedu (Rena Cipta Mandiri, 2025)
Therapeutic communication facilitates nursing actions by a nurse to patients and minimizes the occurrence of errors and misunderstandings in the process of nursing actions. Good knowledge of therapeutic communication will have a positive impact on nurse behavior. The application of therapeutic communication by nurses is one form of real performance from nurses to patients. This research uses descriptive quantitative method and cross sectional research design. The population in this study was the nursing profession students of the Class of 2017 totaling 89 students who were practicing. The research sample was taken using non-probability sampling purposive sampling type. Research shows that there is a relationship between knowledge of therapeutic communication and application of therapeutic communication to nursing profession students (P value = 0.000) which means there is a significant positive relationship between knowledge of therapeutic communication and application of therapeutic communication. The conclusion of this study is that there is a significant relationship between the level of knowledge about Therapeutic Communication and the Application of Therapeutic Communication in Indonesian Medical Student Nurse Profession Stikes in 2022.